(untitled) (Fiep Bulletin - online, 2015)
This study aims to determine the cardiorespiratory system by PowerLab between relieving massage and hot stone therapy. The cardiorespiratory system is to transport oxygen through the cardiovascular system to oxygenate all peripheral tissue including muscle tissue . The anti-stress massage ( NESSI , 2010) is a manual technique that interferes the cardiorespiratory system , it allows to reduce tensions as having therapeutic effect , eliminating the catabolic that are formed in the muscles . Among other therapies there are the hot stones ( SZERMAN , 2013) which is a massage performed with specific instruments for technical stones , in the body producing organic and physiological responses . With the use of hot stones , circulation is increased rapidly , consequently happens a contribution of nutrient benefiting a detoxification in the body . And to analyze the frequency of cardiorespiratory stress-relieving massage techniques and Hot Stone Therapy , the PowerLab is a system designed for use in life science research and application in teaching to examine cardiovascular effects was used . The anti-stress massage showed significant responses to the cardiac system , but the hot stone therapy there was improvement in the respiratory system and the systolic blood pressure decreased by 9.6 % between pre and post , as the diastolic blood pressure showed no significant manifestations . We can conclude that the hot stone therapy and massage antistress feature immediate cardiorespiratory and metabolic responses to physiological well-being and relaxation , need to evaluate the results of medium and long term .